Impact of Oil Factor on Investment: The Case of Azerbaijan - Humbatova, Sugra; Huseyn, Afag; Hajiyev, Natig Gadim‒Oglu (International Journal of Energy Economics and Policy, 2023)
This article investigates the long-term and short-term interactions between crude oil prices, crude oil exports, and domestic and foreign investment in Azerbaijan using annual data from 1999 to 2021. In this research, the ARDL model was used to assess co-integration and short-term relationships. In addition, this study used the FMOLS, DOLS, and CCR co-integration equations to explore long-term coefficients between variables. Granger causation tests were performed, Granger causation analysis was assessed using the Wald test (short-term or weak causation, long-term causation, and both short-term and long-term causation or strong causal relationship). The study proposed 9 hypotheses regarding the impact of oil prices and oil exports on domestic and foreign investment. Some of the hypotheses were generally, if not completely, justified. Based on the established models and tests carried out, there are co-integrating relationships between the variables. Model coefficients are selected according to their economic and statistical significance. It is necessary to increase competition for the market between foreign and domestic investments, not only through the exchange rate, but also through other economic instruments. The study revealed the importance of the exchange rate of the Manat.